2008
DOI: 10.1177/097265270700700102
|View full text |Cite
|
Sign up to set email alerts
|

Market Efficiency in Emerging Stock Market

Abstract: This study seeks evidence on whether the return series on Bangladesh's Dhaka Stock Exchange (DSE) is independent and followsthe random walk model. The study focuses on assessing if the DSE deviates from idealised efficiency. The sample primarily includes all the listed companies on the DSE daily price index over the period 1988 to 2000. The results of both non-parametric (Kolmogrov-Smirnov: normality test and run test) and parametric test (Auto-correlation test, Autoregressive model, ARIMA model) provide evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Many studies suggest inefficiency or a lower level of efficiency in emerging markets compared to developed markets (See for example,Fillis, 2006;Mobarek, Mollah, and Bhuyan, 2008, Risso, 2009) while others contradict this claim (see, for example,Karamera, Ojah, and Cole, 1999;Griffin, Kelly, and Nardari, 2010). However, there is agreement on the heterogeneous levels in efficiency across these markets.…”
mentioning
confidence: 90%
“…Many studies suggest inefficiency or a lower level of efficiency in emerging markets compared to developed markets (See for example,Fillis, 2006;Mobarek, Mollah, and Bhuyan, 2008, Risso, 2009) while others contradict this claim (see, for example,Karamera, Ojah, and Cole, 1999;Griffin, Kelly, and Nardari, 2010). However, there is agreement on the heterogeneous levels in efficiency across these markets.…”
mentioning
confidence: 90%
“…There are some actions (Hussain, Chakraborty, & Kabir, 2008) which can improve the efficiency of the DSE market such as: ensuring asymmetric information among all investors, proper implication of rules of regulatory commission and introducing sophisticated means of investment and tools. Mobarek, Mollah, Sabur and Bhuyan (2008) searched for the independence and randomness in the return series of DSE market by using both non-parametric and parametric tests and noticed that the security returns do not follow random walk model. Alam, Yasmin, Rahman, and Uddin (2011) found that the frequency distribution of the stock prices in DSE does not follow a normal or uniform distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to DSE index returns, Mobarek et al (2008) examine individual stock returns from 1988-2000 provided by a data vendor. Even allowing for structural changes following the 1996 crash, they find that there is significant auto correlation over the sample period.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis updates the sample time period, and following the suggestion of Mobarek et al (2008), examines the dynamics of individual stock price data obtained directly from the exchange. This allows us to also adjust for dividends, share splits, and other corporate events.…”
Section: Introductionmentioning
confidence: 99%